Vilazodone Effective and Safe in Major Depressive Disorder - Hoyle, Brian (MD Conference Express, 2014)
A multicenter, randomized, double-blind, placebo-controlled trial involving more than 1100 patients with major depressive disorder has affirmed the efficacy and safety of vilazodone 40 mg/day and indicated the acceptability of a dose of 20 mg/day [APA 2014 (poster NR6-103)].